Analysis of Aconitine Metabolites in Ten-Year Aconitine Poisoning Human Liver Sample Using High Performance Liquid Chromatography-Tandem Mass Spectrometry - Liu, Yong-Gang; Zhang, Qun-Shu; Lu, Ying-Qiang; Zuo, Min; Zhang, Guo-Zhong; Zhang, Hong-Gui (Asian Journal of Chemistry, 2014)
Described here is a fatal case of accidental aconitine poisoning in a patient who took traditional Chinese medicine (TCM) formula containing radix aconite, radix aconite laterals preparation and radix aconite kusnezoffii ten years ago. The patient fell into a coma and died of brain edema 5 h after diagnosis. Consent for autopsy was confirmed by the family, the toxicity of aconitine alkaloids in the liver was analyzed by LC-MS. According to MS/MS and MS3 spectra data, three metabolites were identified as aconitine (A), benzoylaconine (B) and 16-O-demethylaconitine (C), respectively through comparison with authentic substances and among them, 16-O-demethylaconitine was reported for the first time. Metabolic pathway of aconitine in human liver was proposed. In this paper, the test sample is the longest storage time of all reported samples, so the result is useful to solve many long unsettled law cases of accidental or intentional aconitine poisoning which were caused for obsolete method.